Identification of frequently consumed commercially prepared ready-to-eat foods and beverages in Bangladesh: Identification of frequently consumed RtE foods - Choudhury, Sohel Reza; Shamim, Abu Ahmed; Shaheen, Nazma; Bahar, Nisarga; Sarwar, Sneha; Ashraf, Md Musharraf; Mamun, Mohammad Abdullah Al; Sobhan, Sheikh Mohammad Mahbubus; Abedin, Md Joynul; Hossen, Kabir; et al. (Bioresearch Communications, 2021)
Ready-to-eat processed foods and beverages are eaten without further cooking or processing. These are generally energy-dense and contain a high amount of saturated fat, sodium, and added sugar. The consumption pattern of these foods varies regionally, seasonally, and agewise. The present study aims to identify commercially prepared ready-to-eat processed foods and beverages frequently consumed by different age groups in rural and urban areas of Bangladesh during the month of Ramadan and the non-Ramadan period. In this cross-sectional study, 948 individuals from 480 households in all eight administrative divisions of Bangladesh were interviewed during the month of Ramadan and the Non- Ramadan period. We identified puffed rice, peyaju, chanachur, chips, unbranded ice cream to be the overall highly consumed foods, consumed by 46.3, 40.1, 39.6 38.0, and 33.1 percent respondents, respectively. Consumption of foods other than puffed rice was significantly different across the age groups (p<0.05). A significantly higher number of respondents consumed puffed rice, deep-fried foods (peyaju, beguni, jilapi), and branded ice cream during Ramadan as compared to the non-Ramadan period (p<0.05). It was also found that the overall consumption rate of packaged items was higher among the urban population as compared to the respondent living in rural areas. When the foods were scored according to their consumption rate stratified by age, fasting, and regions, puffed rice, chips, chanachur, unbranded ice cream, peyaju were found to be top foods. Considering frequent intake of processed foods their nutrient composition should be analyzed to know their healthiness. Bioresearch Commu. 7(2): 1019-1030, 2021 (June)